2017
DOI: 10.1038/s41598-017-11580-8
|View full text |Cite
|
Sign up to set email alerts
|

Caring Cooperators and Powerful Punishers: Differential Effects of Induced Care and Power Motivation on Different Types of Economic Decision Making

Abstract: Standard economic theory postulates that decisions are driven by stable context-insensitive preferences, while motivation psychology suggests they are driven by distinct context-sensitive motives with distinct evolutionary goals and characteristic psycho-physiological and behavioral patterns. To link these fields and test how distinct motives could differentially predict different types of economic decisions, we experimentally induced participants with either a Care or a Power motive, before having them take p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…Research in behavioural economics has shown that 79% of the variation in social preferences across a suite of experimental economic games can be explained by two factors: a willingness to pay a cost to benefit others (cooperation dimension) and a willingness to pay a cost to punish normviolators (conformity dimension) 105 . Subsequent studies have replicated this two-factor structure 106,107 across multiple cultures 108 , and such individual differences are heritable 109,110 , remain stable over long periods of time 105,111 , and covary with basic neurological differences 112,113 .…”
Section: This Left-right Distinction Dates Back At Least 200 Years Tomentioning
confidence: 87%
See 1 more Smart Citation
“…Research in behavioural economics has shown that 79% of the variation in social preferences across a suite of experimental economic games can be explained by two factors: a willingness to pay a cost to benefit others (cooperation dimension) and a willingness to pay a cost to punish normviolators (conformity dimension) 105 . Subsequent studies have replicated this two-factor structure 106,107 across multiple cultures 108 , and such individual differences are heritable 109,110 , remain stable over long periods of time 105,111 , and covary with basic neurological differences 112,113 .…”
Section: This Left-right Distinction Dates Back At Least 200 Years Tomentioning
confidence: 87%
“…An understanding of the fitness trade-offs associated with the evolution of cooperation and group conformity makes sense of stable individual differences in economic decisionmaking, personality traits, and neurophysiology, and explains why this variation reliably correlates with political ideology. People show stable individual differences in both cooperation and norm-enforcing punishment in experimental economic games [105][106][107][108] and these individual differences correlate with social values related to taxation and helping (cooperation) and revenge (norm-enforcing punishment) in real world settings 105 . People also exhibit stable variation in personality traits like Machiavellianism and openness to experience, and these traits correlate with economic and social conservatism, respectively 143,144 .…”
Section: Respect For Tradition (Preservation Of Timehonoured Customs)mentioning
confidence: 99%
“…The motive we refer to here as care has been referred to by H. Heckhausen as "help" (1989) and J. Heckhausen as "prosocial altruism" (2000) and finally as "compassion" (Goetz et al 2010;Condon and Feldman Barrett 2013;Crocker and Canevello 2012). This motive has recently been investigated by experimental economists (Bault et al 2017;Chierchia et al 2017;Ring et al 2018). 3 Care is closely related to the economic conception of altruism (Andreoni, 1990; based on, e.g., Edgeworth 1881) in which the well-being of other people enters one's own utility positively.…”
Section: The Fingerprint Of Preferences Under Care: Action Tendenciesmentioning
confidence: 99%
“…Indeed, high-ranking individuals are more likely to detect cheating among low-ranking individuals compared to vice-versa [24], and the powerful appear particularly sensitive to self-relevant offenses [25]. Additionally, third parties expect that high-ranking individuals are more likely to punish norm violations [26] and, indeed, individuals primed with power motives engage in more punishment in social exchange tasks [27]. Moreover, given their increased access to valued resources, high-power individuals might be less sensitive to the costs of punishment and retaliation (i.e., counter-punishment) [26,28] by low-power others.…”
Section: Asymmetric Power and Strategies To Promote Cooperationmentioning
confidence: 99%